2011
DOI: 10.1007/s11427-010-4123-0
|View full text |Cite
|
Sign up to set email alerts
|

Current advances in the application of proteomics in apoptosis research

Abstract: Apoptosis, or programmed cell death, is a complex, genetically-determined process involved in the development and maintenance of homeostasis in multicellular organisms. Dysregulation of apoptosis has been implicated in a number of diseases, including cancer and autoimmune disease. Thus, the investigation of apoptotic regulation has evoked considerable interest. Many apoptotic proteins have been shown to be post-translationally modulated, such as by protein cleavage, translocation, protein-protein interaction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 97 publications
0
1
0
Order By: Relevance
“…Cell biology approaches supported this contention and showed that medium conditioned by apoptotic EC regulates the survival and differentiation of major cellular constituents of the vessel wall (Cailhier et al, 2006;Laplante et al, 2005;Raymond et al, 2004;Soulez et al, 2010). Execution of the apoptotic program relies mainly on post-translational modifications, such as protein-protein interactions, protein translocation and proteolysis that will set in motion the molecular pathways regulating the various phases of apoptosis (Thiede and Rudel, 2004;Wang and Chen, 2011;Mahrus et al, 2008). The caspase family of cysteine proteases is central to the regulation of the various phases of apoptosis.…”
mentioning
confidence: 97%
“…Cell biology approaches supported this contention and showed that medium conditioned by apoptotic EC regulates the survival and differentiation of major cellular constituents of the vessel wall (Cailhier et al, 2006;Laplante et al, 2005;Raymond et al, 2004;Soulez et al, 2010). Execution of the apoptotic program relies mainly on post-translational modifications, such as protein-protein interactions, protein translocation and proteolysis that will set in motion the molecular pathways regulating the various phases of apoptosis (Thiede and Rudel, 2004;Wang and Chen, 2011;Mahrus et al, 2008). The caspase family of cysteine proteases is central to the regulation of the various phases of apoptosis.…”
mentioning
confidence: 97%